Internet Usage Behavior to Determine Network Performance: Case Study in Polytechnic Tuanku Syed Sirajuddin Network - Hai Kelian, Virakwan (2011)
Most of the institutions included education institutions heavily rely on networks to distribute information and to get job done. Polytechnic Tuanku Syed Sirajuddin (PTSS) is one of the educational institution that used network for educational and for effectiveness of institution operational. However, the effectiveness of PTSS operational was disturbed due to the network performance become slowly. To maintain the effectiveness, it is important to monitor how the network system working and used by users. The early observation found that, one of the possible problems impacts the network performance is users bad behavior. To overcome the problems, Cymphonix network monitoring tool used in this study to monitor the network. This study only focuses on network VLAN 20. Monitoring was done during five working days in semester study within office working hours. The main data capture from monitoring tool used in this study are total Internet traffic, application bandwidth and types of application that appear in the network VLAN 20. The data captured were analyzed to identify the Internet application types and relate it to the behavior of the network users. Result from the study indicates that Internet application traffic in network VLAN 20 is fluctuating for every day. Most of the traffic is from HTTP application. Main activities of users in network VLAN 20 is only web browsing and download files. Moreover, the traffic of application that can causes of network performance become slow such as P2P and streaming media are not much consume the range of bandwidth. This is shows that behavior of the users in network VLAN 20 is not main factors that cause network performance in PTSS slow. However, there are some further studies required to identify main causes that contribute to the network problems in PTSS such as used other type of tool that enable to capture all the uncategorized traffic and study on other VLAN network in PTSS to evaluate whether users in that VLAN network causes negative impact to the performance of network in PTSS.